2015
DOI: 10.1007/s00705-015-2620-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and sequence analysis of the complete NS1 and VP2 genes of canine parvovirus from domestic dogs in 2013 and 2014 in China

Abstract: Canine parvovirus (CPV) can cause severe disease in animals and continuously generates new variant and recombinant strains in dogs that have a strong impact on sanitation. It is therefore necessary to investigate epidemic CPV strains to improve our understanding of CPV transmission and epidemic behavior. However, most studies have focused on the analysis of VP2, and therefore, information about recombination and relationships between strains is still lacking. Here, 14 strains of CPV were isolated from domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…The results of the NS1 phylogenetic analysis revealed that the genome characterization of CPV‐2 showed regional distribution differences, but the trend of the time distribution was not obvious. In a previous study, new CPV‐2a and new CPV‐2b formed monophyletic groups in the NS1 phylogenetic tree (Wang, Jin, et al., ), while only CPV‐2c could form monophyletic clusters, in both Clade 1.1 and Clade 1.2, in this study. It is consistent with the result of the VP2 phylogenetic analysis that the Europe and America CPV‐2c and Asia CPV‐2c mainly clustered in Clade 2 and Clade 1.1, respectively.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The results of the NS1 phylogenetic analysis revealed that the genome characterization of CPV‐2 showed regional distribution differences, but the trend of the time distribution was not obvious. In a previous study, new CPV‐2a and new CPV‐2b formed monophyletic groups in the NS1 phylogenetic tree (Wang, Jin, et al., ), while only CPV‐2c could form monophyletic clusters, in both Clade 1.1 and Clade 1.2, in this study. It is consistent with the result of the VP2 phylogenetic analysis that the Europe and America CPV‐2c and Asia CPV‐2c mainly clustered in Clade 2 and Clade 1.1, respectively.…”
Section: Discussionsupporting
confidence: 66%
“…Most of the Chinese CPV‐2 strains identified in recent years were in Clade 1.2 and Clade 2. It has been reported that the relationships between VP2 genes among CPV‐2 strains may not be representative of the relationships between NS1 genes among CPV‐2 strains (Wang, Jin, et al., ). The same conclusion was reached in this study.…”
Section: Discussionmentioning
confidence: 99%
“…3 FPLV infections in large carnivores, such as captive tigers and lions, have been described based on clinical, serological and virological data. [4][5][6][7] However, the number of FPLV strains isolated from the adaptive carnivore species and the molecular information associated with these isolates are very limited. Clinical and etiological investigations are very important for discovering the mechanism(s) underlying the genetic evolution and pathogenicity of FPLV.…”
mentioning
confidence: 99%
“…The filtered homogenates of positive intestinal samples were used to inoculate a Crandell-Rees feline kidney cell monolayer as described previously. 6,7 Cytopathogenic effects were observed in infected Crandell-Rees feline kidney cells beginning 36 h post inoculation (Supplementary Figure S2). The presence of parvovirus in the supernatant of the cell cultures was confirmed by PCR.…”
mentioning
confidence: 99%
“…There has also been a recent CPV-2c epidemic in Vientiane, Laos [64] and Taiwan [65] . In China's capital city, Beijing, CPV-2a and 2b remain the dominant types of this virus [47,[66][67][68] , but more recently, the presence of CPV-2c has been confirmed in China [9,[69][70][71] . In India and Iran, the dominant types in recent outbreaks were CPV-2a and -2b [21,72,73] .…”
Section: Prevalence Of Canine Parvovirus Type 2 Variantsmentioning
confidence: 99%